Research progress of exosomes from different sources in myocardial ischemia - Yan, Huan; Ding, Huang; Xie, Ruo-Xi; Liu, Zhi-Qing; Yang, Xiao-Qian; Xie, Ling-Li; Liu, Cai-Xia; Liu, Xiao-Dan; Chen, Li-Yuan; Huang, Xiao-Ping (Frontiers in Cardiovascular Medicine, 2024)
Ischemic heart disease refers to the imbalance between the supply and demand of myocardial blood; it has various causes and results in a class of clinical diseases characterized by myocardial ischemia (MI). In recent years, the incidence of cardiovascular disease has become higher and higher, and the number of patients with ischemic heart disease has also increased year by year. Traditional treatment methods include drug therapy and surgical treatment, both of which have limitations. The former maybe develop risks of drug resistance and has more significant side effects, while the latter may damage blood vessels and risk infection. At this stage, a new cell-free treatment method needs to be explored. Many research results have shown that exosomes from different cell sources can protect the ischemic myocardium via intercellular action methods, such as promoting angiogenesis, inhibiting myocardial fibrosis, apoptosis and pyroptosis, and providing a new basis for the treatment of MI. In this review, we briefly introduce the formation and consequences of myocardial ischemia and the biology of exosomes, and then focus on the role and mechanism of exosomes from different sources in MI. We also discuss the role and mechanism of exosomes pretreated with Chinese and Western medicines on myocardial ischemia. We also discuss the potential of exosomes as diagnostic markers and therapeutic drug for MI.In this article, the roles and mechanisms of exosomes from different sources in the treatment of MI are reviewed.